Forearmed and Deceived: Diagnosis? - LJ Miedzinski; J Mahood; M Sin; G Sterling (Canadian Journal of Infectious Diseases)
A 58-year-old male with a four-year history of noninsulin dependent diabetes presented in early January 1999 with a two-week history of progressive right fore arm swelling, pain, and limitation of wrist and elbow movement unassociated with recognized trauma. He had been febrile in the three days before the evaluation, despite having been on an anti-inflammatory medication for approximately one week. Progressive clinical worsening in association with a markedly elevated erythrocyte sedimentation rate prompted referral to an infectious diseases consultant regarding the possibility of osteomyelitis.